Local community perceptions on human wildlife interactions in the face of climate variability. A case of Nyaminyami community, Zimbabwe - Mupunga, Power; Shoko, Joseph (Frontiers in Sustainable Tourism, 2024)
Human interactions with wildlife, both positive and negative, have defined the nature of human wildlife relations throughout history. Along with human wildlife interaction, Climate change exacerbates the complexity and consequences of human wildlife interactions, particularly those that rely on flora and fauna for tourism and development. This study assesses the interrelatedness and causes of human wildlife interactions and climate variability and the impact they have on livelihood. Two hundred and fourteen people randomly selected from four wards in the Nyaminyami community in Mashonaland West, Zimbabwe were interviewed. Four focus group discussion sessions with randomly selected residents were also conducted in each ward. Results from the study show that respondents were concerned that human wildlife interactions resulted in human wildlife conflict, and that anthropogenic factors contributed immensely to an increase in the problems faced by local communities. Most of these concerns stemmed from specific areas (wards) where factors such as competition for resources, settlement in wildlife corridors, agricultural activities, tourism and increasing human induced climate change are accelerating human wildlife conflict. Results also show that human related practices contributed to human wildlife interaction in all the four wards. Discussants reported climate change, competition over resources and living close to protected areas as the major factors influencing human-wildlife conflict. It is recommended that communities be educated on, and need to embrace climate change and adapt to it. It is also important that any tourism ventures in the district involve the communities so that they directly benefit from and see the value of living with wildlife and learn to coexist. Proper land use planning is also paramount before any settlements are allocated to avoid living close to protected areas.